Website-Based Customer Relationship Management Modeling At Ar-Rasyid Islamic Hospital Palembang - Alzena Aisha Shakira; Ali Ibrahim (SCOPUS ID: 57203129436); Ken Ditha Tania; Ari Wedhasmara; Pacu Putra Suarli (Sistemasi: Jurnal Sistem Informasi, 2023)
Ar-Rasyid Islamic Hospital is an organization in the health sector that supports the health of the people of Palembang City. The increase in hospitals causes stakeholders to choose the best choice among other hospitals. Therefore, hospitals must have a strategy to provide maximum service to stakeholders by implementing a customer relationship management model. With the website-based CRM modeling at the Ar-Rasyid Palembang Islamic Hospital, this is a recommendation for maintaining and increasing patient loyalty. One of them is modeling at the CRM level, where market segmentation is carried out for all groups of patients by means of service automation such as customer service, FAQs, criticism of suggestions, questionnaire polling data using the Community Satisfaction Index, and parts of it, so that it can survive during business competition. After conducting research, it was found that there was an increase in the quality of hospital services because the average per element was on the verge of 80–90%, which had a very good A value. In the context of CRM, this index helps identify the success or failure of CRM modeling in meeting customer needs and expectations. Through CRM modeling with SMIs, companies can identify factors that contribute to customer retention. By understanding customer needs and preferences through the Community Satisfaction Index. With this CRM modeling, it can maintain the existence of the hospital business in the long term and ensure that patients do not switch to competitors.